Observation of successful treatment of the patient with intraventricular hemorrhage - M. V. Berezyuk; O. A. Tsimeyko; V. V. Moroz (Ukrainian Neurosurgical Journal, 2008)
The new method of intraventricular hemorrhages treatment is described. The observation of patient’s with a primary hemorrhage treatment is given, the technique of local fibrinolysis is considered.